Using U-Bolt for Fixing the Axle of Elevator Deviation Pulleys - Trinh, Dong Tinh (Old Journal, 2017)
Deviation pulleys are used on the elevator traction machines to ensure given distance between the suspension ropes attached to elevator car and counterweight or/and to increase the number of suspension rope falls (roping 2:1 or 4:1). With simple structure, the u-bolts are used widely to fix the axle of these pulleys. In many cases, these bolts are selected or made approximately and it can lead to inadequate selection. This paper presents some results of research concerning the calculation of u-bolts for above mentioned purpose with goal to ensure elevator safe performance. Different angles of contact between the rope and the traction pulley were considered to estimate their influence on the stress in the u-bolt and the standard bolt, then gives some recommendations when choosing or making u-bolts for fixing the deviation pulley axle.